How do national cultures influence lay people's preferences toward doctors' style of communication? A comparison of 35 focus groups from an European cross national research. (December 2015) - Rimondini, Michela; Mazzi, Maria Angela; Deveugele, Myriam; Bensing, Jozien
Abstract Background The evidence that inspires and fosters communication skills, teaching programmes and clinical recommendations are often based on national studies which assume, implicitly, that patients' preferences towards doctors' communication style are not significantly affected by their cultural background. The cross-cultural validity of national results has been recognized as a potential limitation on how generally applicable they are in a wider context. Using 35 country-specific focus group discussions from four European countries, the aim of the present study is to test whether or not national cultures influence lay people's preferences towards doctors' style of communication. Methods Lay people preferences on doctor's communication style have been collected in Belgium, the Netherlands, the United Kingdom and Italy. Each centre organized between eight and nine focus groups, where participants (n  = 259) were asked to comment on a video of a simulated medical interview. The discussions were audiotaped, transcribed and coded using a common framework (Guliver Coding System) that allowed for the identification of different themes. Results The frequency distribution of the topics discussed highlights lay people's generally positive views towards most part of doctors interventions. The regression model applied to the Guliver categories highlighted slight national differences and the existence of a cross-cultural appreciation, in particular, of five types of intervention:Doctors attitudes (bothTask-Oriented andAffective/Emotional ), Summarizing, Structuring andProviding solution . Conclusion Lay panels valued doctors' communication style in a similar manner in the countries selected. This highlights the existence of a common background, which in the process of internationalization of heath care, might foster the implementation of cross-national teaching programmes and clinical guidelines.